Pythagorean Fuzzy Strong Bi-ideal and Direct Product of Pythagorean Fuzzy Ideals in Near Ring - Marynirmala, J.; Sivakumar, D. (Communications in Mathematics and Applications, 2021)
In this paper, we introduce the notions of Pythagorean fuzzy strong bi-ideals and Direct Product Pythagorean fuzzy ideals in near ring. Also, study some of their related properties in detail.
Keywords: Strong bi-ideal; Near ring; Pythagorean fuzzy set; Direct product